Morphological, TGA, and FTIR on Rigid Polyurethane Composite Laminated with Untreated and Treated Bamboo Fiber Roof Insulation - Roseli, Adyla Illyana; Mat Hassan, Nik Normunira; Leman, Abdul Mutalib; Abdul Latif, Najibah; Aminanda, Yulfian; Setyanto, Djoko; Tajunnisa, Yuyun; Areerob, Yonrapach; Nukunudompanich, Methawee; Azmi, Muhammad Farid (semarak ilmu, 2024)
The performance of roof insulation such as polyurethane decreased due to problems such as insufficient absorption and poor thermal insulation performance, especially during rainstorms. The aims of this study are to investigate the physical property and its potential reinforced material such as rigid polyurethane doped with treated and untreated bamboo fiber composite (RPU-BF) at different ratios of 0, 25, 30, 35, and 40% of bamboo fibers as an insulation material for roof applications. The bamboo fibers were treated by using silane coupling agent treatment. The rigid polyurethane composite samples were prepared and then laminated bamboo fiber to overcome the sound problem in roofs. The physical characterization was investigated by Water Contact Angle (WCA), the morphological by Scanning Electron Microscopy (SEM), Thermo-gravimetric Analysis (TGA), and Fourier Transform Infrared Spectroscopy (FTIR) Analysis. The results showed that the treated bamboo fiber had a 192.5° water contact angle as a super hydrophobic property due to the presence of the chemical bonds Si-O-Si and Si-O-C in the silane coupling agent treatment. The morphology showed that 30% ratios of RPU-BF-T30 give the smallest pore diameter size. The peak of thermal degradation temperature of untreated and treated bamboo fiber was increased from 320°C to 350 °C with a weight loss of 80% to 50%. The treated bamboo fiber exhibited peaks at 3010–3040 cm-1 were associated with stronger Si-O-Si bonding, indicating the formation of new chemical bonds between bamboo fiber and silane coupling agent due to the ester bond from the cellulose, lignin, and hemicellulose. Thus, there was a similar trend peak in the functional chemical group in the FTIR spectrum of the RPU-BF composite. This result shows that RPU-BF composite had the potential of the optimum ratio of bamboo fiber as an insulation material for local communities and beneficial to the bamboo industry.